Psychological stress impairs short-term muscular recovery from resistance exercise - Stults-Kolehmainen, M. A.; Bartholomew, J. B. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The primary aim of this study was to determine whether chronic mental stress moderates recovery of muscular function, perceived energy, fatigue, and soreness in the first hour after a bout of strenuous resistance exercise.